ABOUT LINGUOCULTURAL CODES AND THEIR TYPES - Buriyev Islom (International Engineering Journal For Research & Development, 2021)
The article provides comments on the formation of linguocultural codes in linguistics, their definitions, linguistics in Uzbek linguistics. It also gives a brief overview of the types of linguomodic codes and their definitions.